REKONSTRUKSI PARADIGMA PEMBANGUNAN NEGARA HUKUM INDONESIA BERBASIS PANCASILA - Dayanto S.H., M.H. (Jurnal Dinamika Hukum, 2013)
This paper tries to formulate a conceptual perspective on the reconstruction development paradigm of Indonesian state of law. Article 1 (3) Constitution of the republic of Indonesia 1945 stated that “Indonesia is a state of law”, but factually, law is highly degenerate compared to other sector. This degenerate can be interpreted as the absence of a clear paradigmatic about how to build and develop the state of law. The reconstruction development paradigm of Indonesian states of law based from the presence of Pancasila as philosofische grondslag of the Indonesian nation. Keywords: reconstruction, state of law, Pancasila